Multiphase cascaded lattice Boltzmann method - Lycett-Brown, Daniel; Luo, Kai H. (Computers & mathematics with applications (1987), 2014)
To improve the stability of the lattice Boltzmann method (LBM) at high Reynolds number the cascaded LBM has recently been introduced. As in the multiple relaxation time (MRT) method the cascaded LBM introduces additional relaxation times into the collision operator, but does so in a co-moving reference frame. This has been shown to significantly increase stability at low viscosity in the single phase case. Here the cascaded LBM is further developed to include multiphase flow. For this the force term is calculated by the interaction potential method, and introduced into the collision operator via the exact difference method (EDM). Comparisons are made with the lattice Bhatnagar–Gross–Krook (LBGK) method, and an MRT implementation. Both the cascaded and MRT methods are shown to significantly reduce spurious velocities over the LBGK method. For the particular case of the Shan–Chen interparticle force term calculation with the EDM, the cascaded LBM is successfully combined with a multiphase method, and shown to perform as well as the more established MRT method. The cascaded LBM is found to be a considerably improved approach to the simulation of multiphase flow over the LBGK, significantly increasing the stability range of both density ratio and Reynolds number. Additionally the importance of including third order velocity terms in the equilibria of both the cascaded and MRT methods is discussed.